Cultivation of gastrointestinal microbiota in a new growth system revealed dysbiosis and metabolic disruptions in carcinoma-bearing rats - Peña-Ocaña, Betsy Anaid; Hoshiko, Yuki; Silva-Flores, Mayel; Maeda, Toshinari; Pérez-Torres, Israel; García-Contreras, Rodolfo; Gutiérrez-Sarmiento, Wilbert; Hernández-Esquivel, Luz; Marín-Hernández, Álvaro; Sánchez-Thomas, Rosina; Saavedra, Emma; Rodríguez-Zavala, José Salud; et al. (Frontiers in Microbiology, 2022)
A challenge in the study of gastrointestinal microbiota (GITm) is the validation of the genomic data with metabolic studies of the microbial communities to understand how the microbial networks work during health and sickness. To gain insight regarding the metabolism present in the GITm, feces from healthy and sick rats with cancer were inoculated in a defined synthetic medium directed for anaerobic prokaryotes growth (INC-07 medium). Significant differences between cultures grown from healthy and sick individuals were found: 1) the consumption of the carbon source and the enzyme activities involved in their catabolism (e.g. sucrase, lactase, lipases, aminotransferases and dehydrogenases), 2) higher excretion of acetic, propionic, isobutyric, butyric, valeric and isovaleric acids; 3) methane production; 4) ability to form biofilms; and 5) up to 500 amplicon sequencing variants (ASV) identified showed different diversity and abundance. Moreover, the bowel inflammation induced by cancer triggered oxidative stress, which correlated with deficient antioxidant machinery (e. g. NADPH-producing enzymes) determined in the GITm cultures from sick individuals in comparison with those from control individuals. Altogether, the data suggested that to preserve the microbial network between bacteria and methanogenic archaea, a complete oxidation of carbon source may be essential for a healthy microbiota. The correlation of 16S rRNA gene metabarcoding between cultures and feces as well as metabolomic data found in cultures, suggest that INC-07 medium may be a useful tool to understand the metabolism of microbiota under gut conditions.